GLYCEMIC VARIABILITY AS A HIDDEN CARDIAC RISK FACTOR IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: THE ROLE OF THE Δ INDICATOR (Global Conference on Medical and Health Sciences, 2026)
Type 2 diabetes mellitus (T2DM) is one of the leading causes of cardiovascular morbidity and mortality worldwide [1, 2]. Beyond glycated haemoglobin (HbA1c), glycemic variability — defined as fluctuations in blood glucose concentrations throughout the day and across days — is increasingly recognised as an important prognostic factor for cardiac complications [3]. Elevated glycemic variability has been associated with increased oxidative stress, autonomic nervous system imbalance, and prolongation of the QT interval, all of which raise the risk of arrhythmias [4, 5].